2012
DOI: 10.1093/aje/kws195
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Confirmed Guillain-Barre Syndrome Following Receipt of Monovalent Inactivated Influenza A (H1N1) and Seasonal Influenza Vaccines in the Vaccine Safety Datalink Project, 2009-2010

Abstract: An increased risk of Guillain-Barré syndrome (GBS) following administration of the 1976 swine influenza vaccine led to a heightened focus on GBS when monovalent vaccines against a novel influenza A (H1N1) virus of swine origin were introduced in 2009. GBS cases following receipt of monovalent inactivated (MIV) and seasonal trivalent inactivated (TIV) influenza vaccines in the Vaccine Safety Datalink Project in 2009-2010 were identified in electronic data and confirmed by medical record review. Within 1-42 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 31 publications
3
55
1
Order By: Relevance
“…However, other studies reported increased rates of GBS during pandemic periods [5,7]. Indeed, a few studies have even found a small but significant increase in the GBS incidence rate after pH1N1 vaccination [8][9][10][11]28,29]. Vaccination for pH1N1 appears to be accompanied by 0.74-2 additional GBS cases per million doses, which are similar to studies of the seasonal influenza vaccine [8,11,30].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, other studies reported increased rates of GBS during pandemic periods [5,7]. Indeed, a few studies have even found a small but significant increase in the GBS incidence rate after pH1N1 vaccination [8][9][10][11]28,29]. Vaccination for pH1N1 appears to be accompanied by 0.74-2 additional GBS cases per million doses, which are similar to studies of the seasonal influenza vaccine [8,11,30].…”
Section: Discussionsupporting
confidence: 62%
“…After the first Korean pH1N1 case was identified on May 2, 2009, the Korea Centers for Disease Control and Prevention (KCDC) began a program of mass influenza vaccination on October 27, 2009. Although several studies have reported that pH1N1 vaccination is not associated with an increase in the risk of GBS, other epidemiologic studies have reported exactly the opposite [5][6][7][8][9][10][11][12]. However, these studies were limited by small GBS and pH1N1 vaccination sample sizes.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, data from the systems monitoring influenza A(H1N1) 2009 monovalent vaccines suggest that the increased risk for GBS is approximately one or two additional cases per 1 million persons vaccinated, which is similar to that observed in some years for seasonal IIV (350)(351)(352)(353)(354)(355)(356). Studies have also shown an increased risk for GBS following influenza infection, of higher magnitude than the risk observed following influenza vaccination (338,357).…”
Section: Guillain-barré Syndrome and Iivmentioning
confidence: 61%
“…This risk is consistent with the level of risk reported by others. Estimates from single-country studies ranged from 1.05 to 4.70, the majority of which reported statistically significant increased risk [23][24][25][26][27][28][29][30][31][32]. Estimates were lower in studies of adjuvanted vaccines (1.05-3.04) [25,31] than in non-adjuvanted vaccines (1.57-4.70) [26][27][28][29][30]32].…”
Section: Discussionmentioning
confidence: 98%